2017
DOI: 10.1021/acs.nanolett.7b02929
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Fibrous Membranes with Rose Spike-Like Architecture

Abstract: Nanoparticles have been used for engineering composite materials to improve the intrinsic properties and/or add functionalities to pristine polymers. The majority of the studies have focused on the incorporation of spherical nanoparticles within the composite fibers. Herein, we incorporate anisotropic branched-shaped zinc oxide (ZnO) nanoparticles into fibrous scaffolds fabricated by electrospinning. The addition of the branched particles resulted in their protrusion from fibers, mimicking the architecture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 26 publications
1
53
0
Order By: Relevance
“…These miRNAs were over-expressed even in patients with early stages of ovarian cancer. The miRNA signatures from exosomes were equivalent from the originating tumour cells, indicating that circulating miRNA profiles precisely reflected the tumour profiles [67]. Following this study, a variety of reports have confirmed the diagnostic potential of circulating miRNAs in body fluids such as serum, plasma, whole blood and urine [68][69][70] as summarized in Table 1.…”
Section: Clinical Relevance Of Cell-free Mirnas In Ovarian Cancersupporting
confidence: 64%
“…These miRNAs were over-expressed even in patients with early stages of ovarian cancer. The miRNA signatures from exosomes were equivalent from the originating tumour cells, indicating that circulating miRNA profiles precisely reflected the tumour profiles [67]. Following this study, a variety of reports have confirmed the diagnostic potential of circulating miRNAs in body fluids such as serum, plasma, whole blood and urine [68][69][70] as summarized in Table 1.…”
Section: Clinical Relevance Of Cell-free Mirnas In Ovarian Cancersupporting
confidence: 64%
“…The branched nanoparticles (spikes length: 1–5 μm; diameter: 50–200 nm) induced heterogeneous crystallization of the polymeric matrix. This three-dimensional composite enhances the mechanical strain and strength and offers excellent antibacterial activity, while supporting the growth of eukaryote cells [ 170 ]. Bounded to Ti surfaces these structures might improve osteocondutivity and inhibit proliferation of prokaryotes.…”
Section: Periprosthetic Infections and Biofilmmentioning
confidence: 99%
“…Furtherore, ZnO NPs are inexpensive and safe; US FDA has enlisted ZnO as GRAS (generally recognized as safe) metal oxide [36]. ZnO NPs have been used in cancer therapy, drug delivery and they posses antibacterial properties [37,38].…”
Section: Zinc Oxide Nanoparticles (Zno Nps)mentioning
confidence: 99%